2016
DOI: 10.1016/j.bmc.2015.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxylated chalcones with dual properties: Xanthine oxidase inhibitors and radical scavengers

Abstract: In this study, we evaluated the abilities of a series of chalcones to inhibit the activity of the enzyme xanthine oxidase (XO) and to scavenge radicals. 20 mono- and polyhydroxylated chalcone derivatives were synthesized by Claisen-Schmidt condensation reactions and then tested for inhibitory potency against XO, a known generator of reactive oxygen species (ROS). In parallel, the ability of the synthesized chalcones to scavenge a stable radical was determined. Structure-activity relationship analysis in conjun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 72 publications
3
39
0
Order By: Relevance
“…Cytotoxicity tests revealed that the most active of these chalcones is noncytotoxic. However, further structure modifications on the chalcone scaffold are needed to optimize the XO inhibitory activity [53]. Later, Xie et al described a synthetic series of hydroxychalcones ( Figure 15) with moderate XO inhibition, and in vitro IC 50 values of 47.3 and 56.8 μM were calculated for the most potent ones.…”
Section: Phenolic Compounds and Analoguesmentioning
confidence: 99%
“…Cytotoxicity tests revealed that the most active of these chalcones is noncytotoxic. However, further structure modifications on the chalcone scaffold are needed to optimize the XO inhibitory activity [53]. Later, Xie et al described a synthetic series of hydroxychalcones ( Figure 15) with moderate XO inhibition, and in vitro IC 50 values of 47.3 and 56.8 μM were calculated for the most potent ones.…”
Section: Phenolic Compounds and Analoguesmentioning
confidence: 99%
“…SAR and molecular docking analyses revealed that 72 possessed a minimum of three hydroxyl groups that are required for XO inhibitory activity (Fig. ) . In 2017, Ali et al.…”
Section: Xanthine Oxidasementioning
confidence: 99%
“…SAR and molecular docking analyses revealed that 72 possessed a minimum of three hydroxyl groups that are required for XO inhibitory activity (Fig. 16) 151. In 2017, Ali et al synthesized a new series of 2-(substituted benzylamine)-4-methylthiazole-5-carboxylic acid as structural analogs of febuxostat.…”
mentioning
confidence: 99%
“…In general, topiroxostat analogues were not as abundant as febuxostat analogues, a typical representative is the pyridyl-1,2,4triazoles reported by Takahiro Sato et al [19] which possess excellent potency ( Figure 1). Furthermore, other XO inhibitors with various structural classes have also been recently published, including isocytosines, [5,[20][21][22] N-(1,3-diaryl-3oxo-propyl)amides, [23] N-acetyl pyrazolines, [24] hydroxylated chalcones, [25] 9-deazaguanines, [26] benzimidazoles, [27] flavonoids, [28,29] fraxamosides, [30] pyrano [3,2-d]pyrimidines, [31] 2-arylbenzo[b]furans [32] , and benzaldehydes. [33] We have focused on the structural modifications of fivemembered ring and the structure activity relationship (SAR) investigations of classical XO inhibitors.…”
Section: Introductionmentioning
confidence: 99%